Es regnete Anfragen und ehe er sich‘s versah, schneite ihm eine Überraschung ins Haus. Zur synchronen Variierbarkeit der Valenz der Witterungsverben - Petra Szatmári (Beiträge zur Allgemeinen und Vergleichenden Sprachwissenschaft)
As a result of grammaticalisation processes, within various constructions the pronoun es could establish itself as the subject of these constructions. Amongst them, verbs describing the weather constitute a rather small and semantically defined verb subclass. The es-subject is regarded as a peripheral subject realisation with an abstract meaning. Since the ‘weather’ verbs are a verb group firmly anchored in the German verb system, analogous to other constructions, their primary valence varies too. The valence enhancement, i.e. the two- or multi-digit usage, allows the ‘weather’ verbs to be used as verbs of visual perception, verbs of movement, and verba dicendi. Based on the verb regnen ‘to rain’, the article more closely examines the synchronous variability of its valence.